Superior rectus recession for hypertropia in thyroid-associated ophthalmopathy - Chen, Ming-Hao; Yan, Jian-Hua (Journal of AAPOS, 2021)
To assess the outcomes of superior rectus–weakening surgery in patients with thyroid-associated ophthalmopathy (TAO). The medical records of patients with TAO who were treated with surgical weakening of the superior rectus muscle at the Zhongshan Ophthalmic Center from 2008 to 2018 were reviewed retrospectively. Data collected included sex, age at surgery, duration of deviation, ocular alignment, ocular motility, surgical procedures, and outcomes. Surgical success was defined as the absence of diplopia and a vertical deviation of ≤5Δ in primary and reading positions. A total of 33 patients (mean age 45.7 years; 17 males) were included. Of the 33 patients, 28 received unilateral superior rectus recession, with a success rate for primary surgery of 79%. The mean preoperative hypertropia of 35.1Δ ± 19.3Δ was significantly reduced to 3.9Δ ± 9.7Δ. Ocular infraduction restriction significantly improved from a preoperative average of −5.3 ± 1.9 to −1.3 ± 1.3 postoperatively. Five patients underwent superior rectus tenotomy, with only 2 cases having a successful final outcome. For 27 of 33 cases, only a single surgery was required; 6 cases required a second surgery. The overall final success rate was 76%. In our study cohort, superior rectus recession with or without traction suture for hypertropia in thyroid-associated ophthalmopathy resulted in a high rate of success.